# Re: ?? Functional Dependency Question ??

From: paul c <toledobythesea_at_oohay.ac>

Date: Tue, 21 Oct 2008 14:22:43 GMT

Message-ID: <TAlLk.2889$fF3.1939_at_edtnps83>

>

> Step 3: Premise XY (the conjunction of X and Y). ...

Date: Tue, 21 Oct 2008 14:22:43 GMT

Message-ID: <TAlLk.2889$fF3.1939_at_edtnps83>

> On Oct 21, 8:15 pm, paul c <toledobythe..._at_oohay.ac> wrote:

*>> David BL wrote:**>>**>> ...**>>***>>> (X->A)(Y->B) : premise**

*>>> RTP: (X->A)(Y->B) -> XY->AB**>>> X->A, Y->B : conjunction elimination**>>> XY : premise**>>> X,Y : conjunction elimination**>>> A : modus ponens on X,X->A**>>> B : modus ponens on Y,Y->B**>>> AB : conjunction introduction**>>> XY->AB : conditional proof**>>> (X->A)(Y->B) -> XY->AB : conditional proof**>> I can see that the second step is eliminating a "conjunction" but the**>> fourth step doesn't seem to me to involve a conjunction.*>

> Step 3: Premise XY (the conjunction of X and Y). ...

But XY (in the usual FD notation) is a union, not a conjunction.

(If step 4 is valid, there must be a subtlety here that goes beyond just conjunction elimination, ie., some other notion must be involved, but so far it could be eludes me.)

thanks,

p
Received on Tue Oct 21 2008 - 16:22:43 CEST